2022
DOI: 10.1111/wrr.13050
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic glycolysis is important for zebrafish larval wound closure and tail regeneration

Abstract: By combining a genetically encoded lactate FRET sensor with chemical inhibitors, we demonstrate a critical role for the Warburg effect and metabolic reprogramming during zebrafish wound closure and tail regeneration..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…The metabolic demands at a site of damage and repair are hugely increased to drive cell proliferation and other repair processes. Just as in rapidly growing cancer where the Warburg effect switches metabolic pathways from the citric acid cycle and oxidative phosphorylation to anaerobic glycolysis, it seems that injury and repair can also lead to a metabolic shift in cells ( Sinclair et al, 2021 ; Scott et al, 2022 ).…”
Section: Altering Metabolism At the Wound Sitementioning
confidence: 99%
“…The metabolic demands at a site of damage and repair are hugely increased to drive cell proliferation and other repair processes. Just as in rapidly growing cancer where the Warburg effect switches metabolic pathways from the citric acid cycle and oxidative phosphorylation to anaerobic glycolysis, it seems that injury and repair can also lead to a metabolic shift in cells ( Sinclair et al, 2021 ; Scott et al, 2022 ).…”
Section: Altering Metabolism At the Wound Sitementioning
confidence: 99%
“…Beyond cell types and signals, fluorescent metabolic sensors have helped decipher the role that glycolysis and other metabolic pathways play in wound healing. For example, work from Enrique Amaya's lab has used a FRET-based sensor for lactate levels to show that these increase transiently after larval zebrafish fin fold amputation, with lactate inhibition leading to an impairment in wound contraction (Scott et al, 2022). Other FRET-based sensors that can measure changes in tension have also been generated in zebrafish (Lagendijk et al, 2017), but these tools have yet to be used under regenerative or reparative conditions.…”
Section: Coordination Is the Key During Wound Repair And Tissue Regen...mentioning
confidence: 99%
“…Metabolic conversion from oxidative phosphorylation to aerobic glycolysis therefore likely serves a key role in regeneration. Studies have previously shown that metabolic transformation to glycolysis is an inevitable initial event during blastema formation and tail regeneration in zebrafish after amputation ( 49 , 50 ). During this process, cells undergo epithelial-mesenchymal transition and dedifferentiation.…”
Section: Tissue Damage and Microenvironmental Changementioning
confidence: 99%
“…During this process, cells undergo epithelial-mesenchymal transition and dedifferentiation. Inhibiting glycolysis leads to the failure of tail regeneration ( 49 , 50 ). In a zebrafish cardiac regeneration model, glycolysis transfer has been found to be concentrated in the vicinity of damaged tissues ( 51 ).…”
Section: Tissue Damage and Microenvironmental Changementioning
confidence: 99%